Which Anti-VEGF Therapy (Ranibizumab, Bevacizumab, or Aflibercept) Demonstrates The Most Cost-Effective Outcomes For Treating Age-Related Macular Degeneration ? : A Systematic Review - Olivia Putri Chairunnisa; Mia Audina; Irawati (The Indonesian Journal of General Medicine, 2025)
Introduction: Age-related macular degeneration (AMD), particularly its neovascular form (nAMD), is a leading cause of irreversible vision loss in the elderly. Anti-vascular endothelial growth factor (anti-VEGF) therapies, including ranibizumab, bevacizumab, and aflibercept, have revolutionized treatment by inhibiting pathological angiogenesis. However, their high costs and varying efficacy profiles necessitate a comprehensive evaluation of cost-effectiveness to guide clinical and policy decisions. Methods: This systematic review adhered to PRISMA 2020 guidelines, analyzing 40 studies from databases like PubMed, Sagepub, and Google Scholar. Inclusion criteria focused on adult AMD patients treated with anti-VEGF agents, reporting both clinical outcomes (e.g., visual acuity, central retinal thickness) and cost data. Data extraction included study design, intervention details, patient demographics, visual outcomes, cost-effectiveness metrics, and adverse events. Results: Bevacizumab emerged as the most cost-effective option, with annual costs significantly lower than ranibizumab and aflibercept (e.g., €27,087/year vs. +€4,000–€6,000). All three agents showed comparable efficacy in visual acuity improvements, though aflibercept required fewer injections (7.0/year vs. ranibizumab’s 5.8/year). Safety profiles were similar, but bevacizumab was associated with marginally higher systemic risks. Economic analyses highlighted bevacizumab’s dominance in incremental cost-effectiveness ratios (ICERs), while aflibercept’s reduced injection frequency offered potential long-term savings. Discussion: Despite bevacizumab’s economic advantages, its off-label status and safety concerns limit universal adoption. Ranibizumab and aflibercept, though FDA-approved, present higher financial burdens. Geographic disparities in drug pricing and dosing regimens further influence cost-effectiveness. Emerging agents like brolucizumab show promise but require long-term safety data. Conclusion: Bevacizumab is the most cost-effective anti-VEGF therapy for nAMD, balancing efficacy and affordability. Policymakers should prioritize its inclusion in formularies, especially in resource-limited settings, while addressing regulatory and safety barriers.